THE RELATIONSHIP BETWEEN DEPRESSION AND CARDIOVASCULAR DISEASES: A REVIEW OF PSYCHOCARDIOLOGICAL MECHANISMS - Kinga Dyndał; Marcelina Broda; Patrycja Jędrzejewska-Rzezak; Aleksandra Mokrzycka; Adam Żuczek; Katarzyna Urbańska; Izabela Szczap; Anna Hawryluk; Olga Żuczek; Kamil Marzec (International Journal of Innovative Technologies in Social Science, 2025)
Background and Aim: Depression and cardiovascular diseases (CVDs) are major global health burdens with significant overlap. Increasing evidence supports a bidirectional relationship between them, driven by shared mechanisms such as HPA axis dysregulation, inflammation, autonomic imbalance, and behavioral risk factors. Depression increases the risk of cardiovascular events and worsens outcomes in CVD patients. This review explores psychocardiological mechanisms behind this comorbidity and assesses the efficacy of pharmacological and behavioral treatments—including cognitive behavioral therapy (CBT), cardiac rehabilitation programs (CRPs), and consultation-liaison psychiatry (CLP)—in improving patient outcomes. Materials and Methods: A narrative review was conducted using sources from PubMed, Scopus, and ClinicalTrials.gov, including meta-analyses, cohort studies, and clinical guidelines. The review focused on the comorbidity of depression and CVD, underlying mechanisms, and the effects of interventions. Results: Depression affects up to 25% of coronary artery disease patients and elevates the risk of adverse cardiac events. Mechanisms include chronic stress, HPA axis hyperactivity, systemic inflammation, and autonomic dysfunction. CBT and positive psychology interventions were associated with reduced myocardial infarction incidence and angina symptoms. CRPs improved quality of life and reduced depression and anxiety. CL psychiatry helped manage psychiatric comorbidities and enhanced adherence in hospitalized patients. Conclusions: Depression is a modifiable, independent risk factor for CVD. Early screening and integrated interventions—including CBT, CRPs, and CL psychiatry—are effective in improving psychological and cardiovascular health. Personalized, multidisciplinary care is essential for optimal outcomes in patients with comorbid depression and CVD.